Four new species of the Oriental genus Siamites Franz (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
Four new species of the rare glandulariine genus Siamites Franz are described: S. langkatensis sp. n. (Indonesia); S. thantonus sp. n. (Thailand); S. sumatrensis sp. n. (Indonesia); and S. sabahensis sp. n. (E Malaysia). The Indonesian species represent the first records of Siamites on Sumatra, and the Malay species is the first Siamites known to occur in Sabah; the number of nominal Siamites species increases to eight.